Questions disputées quomodo Historiam scribere - Alain Boureau (L'Atelier du CRH)
Alain Boureau, not wanting to fix in a text what historical anthropology is for him, kindly accepted to play a little game into the form of an interview about some of the topics discussed during the symposium in 2008. From the “death of anthropology” as an autonomous discipline to the current need of a critical renew toward a discipline at risk of standardization, he comes back to the major stages of his career as an historian: the definition of alter history as well as of scholastic anthropology, the fruitful encounter with psychoanalysis, the gradual shift towards intellectual history.